Changes in physiological indicators of anaerobic performance under normobaric hypoxic exposure - Tambovtseva, R. V.; Voitenko, Y. L.; Laptev, A. I.; Pletneva, E. V. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to determine the level of tolerance of the physiological systems of athletes working in the anaerobic mode to normobaric hypoxic exposure.